AKSELERASI PARIWISATA BERKELANJUTAN DI KOTA PALEMBANG - Eka Hermawanto; Elly Nurlia (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
This research is based on the background of tourism management in the city of Palembang which is still traditional and has not been managed properly. The complete tourism potential in terms of history, nature, and man-made attractions in the city of Palembang still does not bring prosperity to the community. In addition to sustainable tourism-based management is still far from expectations, this condition is exacerbated by the low involvement of the active role of stakeholders as a driver of tourism progress. This study aims to examine the government's efforts in creating sustainable tourism in the city of Palembang by focusing on four aspects, namely tourism infrastructure, information and communication technology (ICT), education, and socio-economic development. The study used qualitative methods, with purposive techniques, where the validity of the data was obtained through triangulation of sources. The results of the study show that tourism infrastructure has not been maximally developed and connectivity between stakeholders is still weak. Then from the ICT aspect, it shows that there is still a lack of use of ICT as a basis for tourism marketing in the current global era. Based on the aspect of education, it can be seen from the cooperation between the Palembang City government and the world of education, and the development of a positive trend of improvement in the economy and people's mindsets that go hand in hand with the government's efforts